Unscheduled News and Market Dynamics - DUGAST, JÉRÔME (Journal of Finance, 2018)
ABSTRACT When unscheduled news arrives, investors react with a stochastic delay yet still may exploit new information. In this context, I study the equilibrium dynamics of limit order markets. Continuous idiosyncratic liquidity shocks result in trades on both sides of the order book. News therefore arrives at random times. Following news, order flows become unbalanced and market depth is consumed, leading to positive covariance between price variability, trading volume, and order book unbalances. Holding the unconditional price variability constant, news frequency has a negative effect on both market depth and the variability‐volume covariance.